2011
DOI: 10.2174/156652311795684777
|View full text |Cite
|
Sign up to set email alerts
|

BMP-9 Induced Osteogenic Differentiation of Mesenchymal Stem Cells: Molecular Mechanism and Therapeutic Potential

Abstract: Promoting osteogenic differentiation and efficacious bone regeneration have the potential to revolutionize the treatment of orthopaedic and musculoskeletal disorders. Mesenchymal Stem Cells (MSCs) are bone marrow progenitor cells that have the capacity to differentiate along osteogenic, chondrogenic, myogenic, and adipogenic lineages. Differentiation along these lineages is a tightly controlled process that is in part regulated by the Bone Morphogenetic Proteins (BMPs). BMPs 2 and 7 have been approved for clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
170
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 149 publications
(180 citation statements)
references
References 145 publications
(249 reference statements)
10
170
0
Order By: Relevance
“…Our previous studies have revealed that BMP9 is one of the most osteogenic factors for inducing osteoblastic differentiation in MSCs Deng et al, 2008;Kang et al, 2004;Luther et al, 2011;Luu et al, 2007). However, the molecular mechanisms underlying BMP9 functions in MSCs remain to be fully elucidated.…”
Section: Hif1a Is Upregulated In Bmp9-stimulated Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have revealed that BMP9 is one of the most osteogenic factors for inducing osteoblastic differentiation in MSCs Deng et al, 2008;Kang et al, 2004;Luther et al, 2011;Luu et al, 2007). However, the molecular mechanisms underlying BMP9 functions in MSCs remain to be fully elucidated.…”
Section: Hif1a Is Upregulated In Bmp9-stimulated Mscsmentioning
confidence: 99%
“…We have found that BMP9 is one of the most potent BMPs among the 14 types of BMPs in inducing osteogenic differentiation of MSCs both in vitro and in vivo by regulating several important downstream targets during BMP9-induced osteoblast differentiation Kang et al, 2004;Luo et al, 2004;Luther et al, 2011;Luu et al, 2007;Peng et al, 2003;Peng et al, 2004;Sharff et al, 2009;Tang et al, 2009). BMP9 (also known as growth differentiation factor 2, or GDF-2) was identified in the developing mouse liver (Song et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…BMP9 has emerged as a powerful growth factor currently at the forefront of bone healing technologies (36) and as a therapeutic target in neurodegenerative disease (37) and cancer (38). Administration of BMP9 holds therapeutic potential in bone and cartilage defects and neurodegenerative disease (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of BMP9 holds therapeutic potential in bone and cartilage defects and neurodegenerative disease (36,37). In addition, targeting BMP9/BMP10 signaling by soluble Alk1-Fc and an ALK1 blocking antibody is explored in cancer treatment (23,38).…”
Section: Discussionmentioning
confidence: 99%
“…They can differentiate into muscle cells, bone cells, or cartilage cells (Luther et al, 2011). MSCs are often used as seed cells in the bone cell regeneration therapy for fracture trauma repair (Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%